2003
DOI: 10.1002/pros.10224
|View full text |Cite
|
Sign up to set email alerts
|

Intraepithelial and stromal lymphocytes in the normal human prostate

Abstract: The immune response in the prostate is primarily cell-mediated. Cell distribution is constant according to patient age, race, and anatomic zonal location within the prostate. The greatest concentration is in the stroma with a small but significant number of intraepithelial cells. The inverted CD4/CD8 ratio in the intraepithelial compartment suggests that cytotoxic/suppressor T cells are the first line of defense against luminal foreign agents reaching the prostate through retrograde flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
52
0
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 24 publications
7
52
0
4
Order By: Relevance
“…A low CD4/CD8 T cell ratio has also been observed in the normal human prostate. 152 Altogether these findings may suggest that prostates in rats that are resistant to inflammation show a cellular profile characterized by high levels of cytotoxic CD8 þ T cells, a high NKT/T-cell ratio, and low CD4/CD8T cell ratio. NKT cells are novel T-cell lineage expressing NK cell markers (CD161a/NKR-P1A in rats).…”
Section: Rat Models Of Prostatitismentioning
confidence: 94%
“…A low CD4/CD8 T cell ratio has also been observed in the normal human prostate. 152 Altogether these findings may suggest that prostates in rats that are resistant to inflammation show a cellular profile characterized by high levels of cytotoxic CD8 þ T cells, a high NKT/T-cell ratio, and low CD4/CD8T cell ratio. NKT cells are novel T-cell lineage expressing NK cell markers (CD161a/NKR-P1A in rats).…”
Section: Rat Models Of Prostatitismentioning
confidence: 94%
“…Although leukcocytes scattered diffusely throughout the tissue were identified in foci of adenocarcinoma, adjacent benign tissue and specimens affected by NHPG, leucocytes organised into follicle-like clusters were barely detected in malignant tissue. Because scattered leukcocytes could be found in prostate tissue even in the absence of cancer, hyperplasia or florid prostatitis (McClinton et al, 1990;Bostwick et al, 2003), we concluded that scattered leucocytes unlikely represent tumour-directed immuneeffector cells. On the contrary, the differences in clustered infiltrates between adenocarcinoma lesions, perimalignant tissue and NHPG were not qualitative (irrespective of their location, clusters were mainly composed of CD4 lymphocytes; Figure 3) but rather quantitative (less intense clusters were detected in malignant lesions; Figure 2), thereby implying a diminished access of immune-effector cells to the tumour core.…”
Section: Discussionmentioning
confidence: 86%
“…Gene expression analysis between the normal peripheral zone (PZ) and transition zone (TZ) of the specimens obtained from prostate cancer patients revealed preferential expression of MIC-1 in the PZ (predominant site of tumor occurrence) compared to the TZ (site of benign prostatic hyperplasia) (26). The expression of MIC-1 is also reported in adult human prostate tissues with the existence of infiltrating lymphocytes in normal-appearing prostate tissues (27,28). An induction in MIC-1 gene expression in kidney, lung and liver tissue due to injury following surgical, chemical or heat shock methods has also been observed (29,30).…”
Section: Modulation Of Mic-1 Expression In a Human Prostate Cancer Cementioning
confidence: 98%